Opinions of Pilots from the Time of World War II on Their Own and Enemy Aircraft - Wybranowski, Dariusz (Tools of War, 2023)
The article largely encompasses quoted opinions of pilots regarding the aircraft they flew in air combat during World War II, both on the Allied and Axis sides. These voices provide an authentic record, sometimes subjective, of the technological transformations that occurred in the military aviation of the warring nations. The article consists of two main parts. The first part presents the opinions and judgments of Allied aviators – Polish, British, French, and Soviet. The second part focuses on pilots from the Axis powers – Nazi Germany, Japan, Finland, and Bulgaria. A significant addition is the third section, which discusses innovative aircraft designs that emerged during WWII, particularly jet-propelled planes, along with pilots' opinions about them. The article also addresses substantial changes in aerial weaponry, notably the various 20 mm cannons that enhanced combat effectiveness in the air and German V-1 and V-2 missiles, detailing methods for countering them and the threats they posed to fighter pilots attempting their destruction. The memoirs of aviators representing both sides of the conflict constitute a vital source for understanding the studied issue. Their opinions and evaluations also contribute significantly to comprehending different stages of aviation technology transformation and development, new aircraft types, and the origins of certain design solutions and aerial combat tactics. Throughout the text, sources such as the memoirs of Witold Urbanowicz, Stanisław Skalski, Jan Zumbach, Tadeusz Kotz, Jan Książczyk (John Bennnett), John Kent, Pierre Clostermann, selected US Air Force pilots, Adolf Dickfeld, Saburo Sakai, Eino Luukkanen, and Stojan Stojanov have been utilized. Episodically, the author has also referred to works covering specific episodes related to WWII in the air, biographies of selected pilots, or monographs on certain aircraft from the years 1939–1945.